2005
DOI: 10.1016/j.jacc.2005.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Ischemia Is a Major Determinant of Transmurality and Severe Microvascular Obstruction After Primary Angioplasty

Abstract: In AMI patients with impaired coronary perfusion undergoing PCI, the risk of TN and SMO increases with the duration of the ischemic time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
127
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(148 citation statements)
references
References 36 publications
18
127
1
2
Order By: Relevance
“…For every 30 minutes of treatment delay, there was a 37% increased risk of transmural necrosis (11).…”
Section: Ormentioning
confidence: 99%
“…For every 30 minutes of treatment delay, there was a 37% increased risk of transmural necrosis (11).…”
Section: Ormentioning
confidence: 99%
“…The rate of the progression of LV systolic dysfunction and its clinical manifestation -heart failure -is determined by the degree and duration of myocardial ischemia, stunning myocardium, the damaged area of the myocardium, the localization of the damage, the degree of infarct-related coronary artery lesion, and changes in the myocardium prior to ACS (8)(9)(10)(11). In the presence of myocardial changes, the course of LV systolic dysfunction is related to the myocardial remodeling process and its consequences, dilatation of cardiac chambers, mitral regurgitation, and diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al questioned whether there is a correlation between delayed contrast enhancement and the age of myocardial infarction, as well as the use of CMR to detect viability and irreversible lesions and evaluate the contractile function of the myocardium. [21][22][23][24] The theory was tested on canine models, and their results revealed that in the first 24 hours from the infarction, hyperenhancement occurs both in the necrosis zone and at the borderline that includes the hibernating myocardium. In terms of chronic infarction, the contrast agent has a strict affinity for the fibrosis area, and the imaging delineation of the hibernated myocardium from the necrosis area is a real challenge.…”
Section: Clinical Applications Of Cmrmentioning
confidence: 99%